THE BEGINNING AND DEVELOPMENT OF ENGLISH BOYS’ AND GIRLS’ SCHOOLS AND SCHOOL LIBRARIES IN THE STRAITS SETTLEMENTS, 1786-1941 - Lim, Peng Han (Malaysian Journal of Library and Information Science, 2009)
Throughout the nineteenth century missionaries from Europe and America dominated the setting up of English boys’ and girls’ schools in the Straits Settlements. In 1899 there were only two known school libraries. During the 1930s more than 70 per cent of English schools had school libraries. In 1937 80 per cent of English Boys’ schools had school libraries. However, by 1935 97 per cent of Malay vernacular boys’ schools had school libraries since they were funded by the Government. Several factors impended the development of English school libraries: (a) Most of these schools collect fees and were partially funded through Government grants; (b) There was no central book-buying agency to coordinate the importation of English books from India and Europe as the publishing and distribution of Malay books were centrally controlled by the Education Department; (c) Government funding for English school libraries began in 1939; Europe was already at war and resources were prioritized for the defense of the settlements; (d) The public libraries in Singapore and Penang did not provide services to school libraries as practiced in England; (e) Although two school library associations were established in England in 1937, the movement did not spread to the settlements.